Gender Differences in Physical Activity Patterns and Cognitive Function Among Middle-Aged and Older Adults: Evidence From the CHARLS - Siyuan Kong; Ran Yan (International Journal of Education and Humanities, 2026)
While the mental health benefits of physical activity (PA) are well documented, evidence regarding the association between specific PA patterns and the risk of cognitive impairment among middle-aged and older adults in China remains limited, particularly with respect to gender differences. This study aimed to examine the relationships between different dimensions of PA—including intensity, frequency, duration, and total volume and cognitive function among Chinese adults aged 45 years and above. Data were drawn from the 2018 wave of the China Health and Retirement Longitudinal Study (CHARLS), comprising a nationally representative sample of 4,160 participants. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), and binary logistic regression models were employed to estimate the associations between PA patterns and the likelihood of cognitive impairment, stratified by gender. The findings indicated notable gender-specific associations. Among men, engaging in light physical activity (LPA) for 3–5 days per week (OR = 0.42, 95% CI: 0.19–0.92), with daily durations of at least 240 minutes (OR = 0.71, 95% CI: 0.40–1.29) and total weekly activity exceeding 1,260 minutes (OR = 0.69, 95% CI: 0.38–1.25), was associated with a lower risk of cognitive impairment. Among women, LPA performed 6–7 days per week (OR = 0.76, 95% CI: 0.57–1.00), with daily durations of at least 240 minutes (OR = 0.71, 95% CI: 0.50–1.02) and either low (<525 minutes) or high (>1,260 minutes) weekly PA volume (OR = 0.72, 95% CI: 0.51–1.03), was linked to reduced impairment risk. In contrast, excessive vigorous physical activity (VPA), defined as more than 240 minutes per day, was associated with an increased risk of cognitive impairment among women (OR = 1.34, 95% CI: 1.00–1.79). Overall, the study highlights the importance of moderate, light-intensity physical activity for cognitive health in later life and underscores the need to consider gender-specific PA recommendations.